CARRYING CAPACITY OF VANNAME SHRIMP (Litopenaeus vannamei) PONDS IN THE ASPECT OF WATER QUALITY AT PURWOREJO VILLAGE, PASIR SAKTI SUBDISTRICT, EAST LAMPUNG DISTRICT - Wuni Alfionita; Ellen Larasati; Agus Arif Rahman; Hengki Pradana (Universitas Teuku Umar, 2025)
The carrying capacity of ponds in vaname shrimp farming is one of the factors supporting the productivity of aquaculture. The purpose of this study was to evaluate the carrying capacity of vaname shrimp ponds in the aspects of water quality to determine efforts to develop vaname shrimp farming based on the carrying capacity of the pond environment. This research was conducted in Purworejo Village, Pasir Sakti District, East Lampung Regency. The research parameters observed included physical, chemical, and biological parameters of water. The results obtained were temperature 29°C, salinity 18.7–19.3 ppt, pH 8.1–8.3, Dissolved Oxygen (DO) 6.0–6.6 mg/l, Total Ammonia Nitrogen (TAN) 0.023–0.083 mg/l, nitrite 0.086–0.149 mg/l, Total Organic Matter (TOM) 63.3–72.3 mg/l, alkalinity 143–165 mg/l, hardness 1860–1933 mg/l, plankton abundance 776 x 103 – 1025 x 103 cell/ml, Total Vibrio Count (TVC) 1.83 x 103 – 2.30 x 103 . The conclusion obtained is that the physical and biological parameters of water quality are in optimal condition for vaname shrimp farming. In chemical parameters, the concentration of TOM exceeds the optimal limit, so it is necessary to do routine flushing and water changes.